2012
DOI: 10.1093/annonc/mds259
|View full text |Cite
|
Sign up to set email alerts
|

The evolving role of immunotherapy in prostate cancer

Abstract: The prognosis for men with metastatic, castration-resistant prostate cancer (CRPC) is limited, and patients have very few treatment options, particularly if the treatment failed with docetaxel (Taxotere). As a result, there is a requirement for novel approaches to therapy. Using immunotherapy to induce immune responses to prostate cancer in preclinical and clinical studies appears to be a valid therapeutic approach. In a pivotal phase III trial, treatment with sipuleucel-T, an autologous cellular vaccine consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 31 publications
1
35
0
1
Order By: Relevance
“…Nevertheless, PAP is an important therapeutic target for PC, as evidenced by the recent success of immunotherapy based on PAP. Provenge, which is based on PAP-charged autologous cells, has been FDAapproved and commercialized (Gerritsen 2012;Kong and Byun, 2013;Sims, 2012). Moreover, a PAP encoded DNA vaccine is currently undergoing clinical trials to prevent and treat PC (Lubaroff, 2012;McNeel et al, 2009) An RNA aptamer is similar to an antibody with a wide range of target recognition sites and a variety of applications.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, PAP is an important therapeutic target for PC, as evidenced by the recent success of immunotherapy based on PAP. Provenge, which is based on PAP-charged autologous cells, has been FDAapproved and commercialized (Gerritsen 2012;Kong and Byun, 2013;Sims, 2012). Moreover, a PAP encoded DNA vaccine is currently undergoing clinical trials to prevent and treat PC (Lubaroff, 2012;McNeel et al, 2009) An RNA aptamer is similar to an antibody with a wide range of target recognition sites and a variety of applications.…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis of thiosemicarbazone derivatives (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) was carried out according to the steps depicted in Scheme 1. In the initial step, 4-(naphthalen-1-yl)thiosemicarbazide (A) was synthesized via the reaction of 1-naphtyl isothiocyanate with hydrazine hydrate.…”
Section: Resultsmentioning
confidence: 99%
“…After it was found that the growth of prostate cancer had been androgensensitive, hormonal therapy was used to treat metastatic disease. At first all patients with prostate cancer responded to hormonal therapy but then the majority gradually developed resistance so it has turned out an obligation to find out new ways for the treatment of prostate cancer [2][3][4][5][6][7][8] . Thiosemicarbazones possess a wide range of pharmacological effects including antineoplastic, antibacterial, antifungal and antiviral activity and they give rise to a great variety of coordination modes depending on their chemical structure.…”
Section: Introductionmentioning
confidence: 99%
“…40 In the majority of the clinical trials, the focus is on serum PSA responses, humoral responses as well as T cell activation or CD4-responses. 19 , 28 , 29 , 41-44 No autologous tumors were available from the patients from this trial, making it impossible to test whether the CD8 + T cells recognizing antigens in the UbiLT3 DRibble vaccine could also recognize and kill autologous tumor cells. The lack of primary tumor also prevented the search for patient-specific neo-epitopes and CD8 + T cells recognizing such epitopes.…”
Section: Discussionmentioning
confidence: 99%